Integrating flipped PDF professional to develop a PBL e-worksheet for students’ critical thinking - Widiyaningsih, Budi; Suyitno, Hardi (Universitas Ahmad Dahlan, 2024)
Increasingly advanced and developing technology resulted in the rapid development of science. Students have used smartphones a lot with the help of the internet to learn and obtain information. The impact of the covid pandemic has affected the use of technology. Digital-based teaching materials are needed to support student learning activities. One of the schools that will be used as a research location is SMP Nurul Muttaqin. This study aims to develop a valid, practical and effective Problem Based Learning (PBL) based e-worksheet to improve students' critical thinking skills towards quadrilateral math material. In this study using qualitative methods with the development of 4-D (Four-D Models), namely define, design, develop and disseminate. The instruments used in the study were media expert and material expert validation sheets, student response questionnaires and questions to measure students' problem-solving abilities. PBLbased E-worksheet is said to be valid in terms of media 111.5 with good criteria, and material expert validation obtains an average score of 51 with good criteria. From these results the developed e-worksheet can be declared to meet the validity criteria for a teaching material. Based on the results of the questionnaire the responses of e-worksheet students were said to be practical by small groups and large groups. Based on the student response questionnaire, the small group obtained an average score of 49,2 with good criteria, and the large group obtained an average score of 51.3 with good criteria. In this study, the effectiveness of the e-worksheet was obtained through post-test questions from the treatment group and control group using the independent sample t test and obtained tcount > ttable, so h0 was rejected, which means that learning with treatment groups using the pbl model assisted by eworksheet is effective. to increase the critical thinking of class vii students of smp nurul muttaqin compared to the control group that does not use e-worksheet.